Analisis Keterampilan Passing Atas Permainan Bola Voli Pada Extrakurikuler di SMA Negeri 1 Toboali - Muris Dinata; Yasir Arafat; Farizal Imansyah (Universitas Maritim AMNI Semarang, 2024)
This research aims to determine passing skills in extracurricular volleyball games at SMA Negeri 1 Toboali. In this research, the method used is a quantitative method which tries to describe the passing skills of SMA Negeri 1 Toboali. The population in this study were students who took part in extracurricular volleyball at SMA Negeri 1 Toboali, totaling 23 students, and the sample in this study was 23 people, there were 13 men while there were 10 women. The data collection technique used in this research was a passing test over a volleyball game. The data analysis technique uses descriptive statistical analysis. This analysis uses the Excel application and manual calculations. Based on the data analysis carried out in this research, it can be concluded that of the 23 volleyball extracurricular students at SMA Negeri 1 Toboali, the results of their volleyball passing skills were in the very high category, with a percentage of 87.3%. This can be seen from the percentage results of each sub-indicator (assessment). In the initial attitude indicator the percentage is 50%, in the core attitude indicator (implementation) the percentage is 82%, and in the final (advanced) attitude indicator the percentage is 56%.